Effect of quality standards in health care services on the motivation of employees; an implementation at private hospitals within the province of Istanbul - Tamer, Gülay (İstanbul Gelişim Üniversitesi Yayınları / Istanbul Gelisim University Press, 2021)
This study aims to evaluate the effect of quality in health standards implemented at health institutions on the motivation of healthcare professionals. Method: The universe of this study consists of 202 healthcare professionals working at the private Medicana Bahçelievler Hospital operating at European Side of Istanbul with the 898 approval number on the date of 12.03.2019. In this research, the responses of the participants for the questions of the questionnaire were analyzed by the use of AMOS 24.0, and SPSS for Windows 22.00 programs. The subdimensions of quality standards in health care services (QSH), and motivation of employees (ME), being the scales used in the research, were determined by exploratory factor analysis, and then the crosscheck of these dimensions was performed by confirmatory factor analysis. Thereafter, values of Cronbach’s alpha, being the reliability coefficient, and composite reliability, and convergence validity were calculated. The effect of quality standards in health care services (QSH) on the motivation of employees (ME) was examined through a structural equation model with implicit variables. And the comparison of all dimensions and subdimensions of the scales of quality standards in health care services (QSH), and motivation of employees (ME) as per demographic attributes was searched by one-way analysis of variance (ANOVA), independent samples t-tests. Results: As a result of the research, it has been observed that the quality standards in healthcare have a significant and positive effect on employee motivation. It was found that the managerial processes dimension of the quality standards in health affects the motivation of the employees in a significant and positive way by using only psychological and social tools, but the use of economic tools and organizational managerial tools among the motivation tools does not affect the motivation of the employee. However, it is seen that quality standards in health do not affect the dimension of educational processes by using psychological and social tools, which are motivational tools, and positively and significantly affect employee motivation by using economic and organizational-managerial tools. Conclusion: According to the demographic attributes of the participants of the research, it was determined that quality standards in health, and motivation of employees were being affected in a positive direction as their education and experiences increase. It was observed that the increase of the age of employees was positively affecting the managerial processes of quality standards in health, but that it wasn’t affecting their motivation. It was determined that the gender of employees wasn’t affecting the quality standards in health, and motivation of employees.

Bu çalışma, sağlık kurumlarında uygulanan sağlıkta kalite standartlarının, sağlık çalışanlarının motivasyon düzeyine etkisini değerlendirmeyi amaçlamaktadır. Yöntem: Bu çalışmanın evreni İstanbul Avrupa yakasında faaliyet gösteren iki özel hastanede çalışan 202 sağlık personelinden oluşmaktadır. 12.03.2019 tarihinde ve 898 onay numarası ile onaylanan bu araştırmada katılımcıların anket sorularına verdiği cevaplar AMOS 24.0 ve SPSS for Windows 22.00 programı desteğiyle analiz edilmiştir. Araştırmada kullanılan ölçekler olan sağlık hizmetlerinde kalite standartları (SKS) ve çalışan motivasyonu (ÇM) ölçeklerinin açımlayıcı faktör analizleri ile alt boyutları belirlenmiş, daha sonra ise bu boyutların doğrulayıcı faktör analizi ile sağlaması yapılmıştır. Sonrasında, güvenilirlik katsayısı olan Cronbach's alpha değerleri ve birleşik güvenilirlik ile yakınsama geçerliliği değerleri hesaplanmıştır. Sağlık hizmetlerinde kalite standartlarının (SKS), çalışan motivasyonuna (MTV) etkisi örtük değişkenlerle Yapısal eşitlik modeli ile incelenmiştir. Sağlık hizmetlerinde kalite standartları (SKS) ve çalışan motivasyonu (ÇM) ölçeklerinin toplam ve alt boyutlarının demografik özelliklere göre karşılaştırması ise Tek Yönlü Varyans analizi (ANOVA) ve independent sample-t (bağımsız örneklem t testi) testleri ile araştırılmıştır. Bulgular: Sağlıkta kalite standartlarının çalışan motivasyonu üzerinde anlamlı ve pozitif şekilde etkilendiği görülmüştür. Sağlıkta kalite standartlarının yönetimsel süreçleri boyutunun, çalışan motivasyonunu sadece psikolojik ve sosyal araçlar kullanılarak anlamlı ve pozitif yönde etkilediği ancak motivasyon araçlarından ekonomik araçlar ve örgütsel-yönetsel araçların kullanılmasının çalışan motivasyonunu etkilemediği bulunmuştur. Ancak sağlıkta kalite standartlarının eğitim süreçleri boyutunu, motivasyon araçlarından psikolojik ve sosyal araçlar kullanılarak etkilemediği, çalışan motivasyonu ekonomik ve örgütsel-yönetsel araçlar kullanılarak pozitif ve anlamlı yönde etkilediği görülmektedir. Sonuç: Araştırmaya katılanların demografik özelliklerine göre; eğitim ve tecrübeleri arttıkça sağlıkta kalite standartlarının ve çalışan motivasyonunun pozitif yönde etkilendiği tespit edilmiştir. Çalışanların yaşlarının artması sağlıkta kalite standartlarının yönetimsel süreçlerini olumlu yönde etkilediği ancak motivasyonlarını etkilemediği görülmüştür. Çalışanların cinsiyetlerinin sağlıkta kalite standartları ve motivasyonlarını etkilemediği tespit edilmiştir.
Sağlık hizmetlerinde kalite standartlarının çalışan motivasyonu üzerindeki etkisi; İstanbul ilindeki özel hastanelerde bir uygulama
Keywords: Health; Quality standards; Motivation; Sağlık; Kalite standartları; Motivasyon